Your creative brain : - Carson, Shelley (Jossey-Bass, 2010)
In " your creative brain" explains seven brain states or "brainsets" and their functions as related to creativity, productivity, and innovation. Provides quizzes, exercises, and self-tests to activate each of these seven brainsets to unlock our maximum creativity. Your Creative Brain, called by critics a ?new classic? in the field of creativity, offers inspiring suggestions that can be applied in both one?s personal and professional life.